Management of immunosuppressants in the era of coronavirus disease-2019. Issue 3 (May 2021) - Manansala, Michael; Baughman, Robert; Novak, Richard; Judson, Marc; Sweiss, Nadera
Abstract : Purpose of review: Patients on chronic immunosuppressive treatments at baseline are at increased risk of opportunistic infections. These patients are at especially increased risk of morbidity and mortality during the coronavirus-19 (COVID-19) pandemic. This review will focus on patients with diseases in which immunosuppression is a vital part of the treatment regimen, including those with solid organ transplants, rheumatologic disorders, sarcoidosis, and inflammatory bowel disease (IBD). We will summarize the current knowledge of immunosuppression in these diseases and the risk of contracting COVID-19. Furthermore, we will discuss if immunosuppression increases severity of COVID-19 presentation. Recent findings: Since the start of the COVID-19 pandemic, a large number patients receiving chronic immunosuppression have been infected with SARS-CoV-2. Moreover, our understanding of the immunology of SARS-CoV-2 is advancing at a rapid pace. Currently, a number of clinical trials are underway to investigate the role of immunosuppressive treatments in the management of this disease. Summary: Currently, there is no conclusive evidence to suggest that solid organ transplant recipients on chronic immunosuppression are at increased risk of contracting COVID-19. Solid organ transplant recipients may be at increased risk for worse COVID-19 outcomes but the data are not consistent. There is evidence to suggest that patients with rheumatologic disorders or IBDs are not at increased risk of contracting COVID-19 and do not necessarily experience worse clinical outcomes. Patients with sarcoidosis are not necessarily at increased risk of COVID-19, although there is limited data available to determine if immunosuppression worsens outcomes in this population.